Lagrangian coherent vortex structures and their numerical visualization - Volkov, K.N.; Emelyanov, V.N.; Kapranov, I.E.; Teterina, I.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2018)
Some issues related to the implementation and physico-mathematical support of computational experiments on the study of fluid and gas flows containing Lagrangian coherent vortex structures are considered. Methods and tools designed to visualize the vortex flows arising in various practical applications are discussed. Examples of visual representation of solutions to gas dynamics problems computed with Lagrangian approaches to the description of fluid and gas flows are given. In addition to the traditional approaches to the visualization of vortex flows based on the construction of contour curves of various flow quantities, the phase trajectories of Lagrangian particles, the Poincar’e sections, and the local Lyapunov exponent method are applied.